Pilgrimage movement in Galicia in the second half of the 19th century and at the beginning of the 20th century in the reports of the Galician press - Biesiadecka, Elżbieta (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
The subject of the research undertaken in the article is the picture of pilgrimages of Galicians and the inhabitants of other partition in the Galician press. Pilgrimages constituted an important aspect of religious life in Galicia and in the second half of the 19th century they started to become mass events. Galician pilgrims travelled not only to holy places located within the partition but also courageously went on pilgrimages to Rome and the Holy Land. The authors of articles pointed out not only the religious dimension of the described Polish pilgrimages but also showed them as the opportunity to cultivate unity and the national tradition and to become more familiar with the national history.

Przedmiotem podjętych badań w niniejszym tekście jest obraz pielgrzymowania Galicjan i mieszkańców pozostałych zaborów przedstawiony w prasie galicyjskiej. Pielgrzymki stanowiły ważny aspekt życia religijnego Galicji, a w drugiej połowie XIX w. zaczęły nabierać charakteru masowego. Galicyjscy pielgrzymi podejmowali wyprawy pątnicze nie tylko do miejsc kultu w obrębie zaboru, ale także odważne wyprawy do Rzymu i Ziemi Świętej. Autorzy artykułów zwracali uwagę nie tylko na wymiar religijny opisywanych przez nich pielgrzymek Polaków do miejsc świętych, ale również ukazywali je jako możliwość kultywowania jedności i tradycji narodowej oraz bliższego poznania ojczystej historii.
Keywords: pilgrimage; Galicia; Galician press; Holy Land; Rome; pielgrzymka; Galicja; prasa galicyjska; Ziemia Święta; Rzym